PENGEMBANGAN MEDIA POCKET BOOK BERINTEGRASI AUGMENTED REALITY PADA MATA PELAJARAN IPAS KELAS V SDN 101837 SUKAMAKMUR - Jessica Sipayung; Lidia Simanihuruk; Imelda Free Unita Manurung; Syahrial; Nurhudayah Manjani (STKIP Subang, 2026)
This study aims to develop an Augmented Reality-integrated pocket book for the IPAS subject, specificaly on the topic of human respiratory organs for Grade V of SDN 101837 Sukamakmur, and to determine its validity, practicality, and effectiveness. The study employed a Research and Development (R&D) method with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The trial subjects consisted of 25 fifth-grade students. The instruments used included expert validation sheets (material and media), teacher and student questionnaires, and test (pre-test and post-test). The result showed that: (1) media validity obtained a percentage of 95% from the material expert and 93% from the media expert, both categorized as very valid, (2) practicality by the teacher reached 95%, and student responses reached 98%, both categorized as very practical, (3) effectivinedd was demonstrated by an increase in the average pre-test score (55,88) to the post-test score (86,15), a classicak mastery rate of 92%, and an N-Gain score of 74% (high category). Based on these findings, the Augmented Reality-integrated pocket book is declared valid, practical, and effective for use in IPAS learning on the respiratory organ material in Grade V of elementary school.